China's Quest for Energy Resources on Global Markets - Konan, D. E. (2012)
Economic prosperity in China is accompanied by a growing demand for energy. Heavily reliant on coal and petroleum, continued growth in Chinese energy use will rapidly increase global greenhouse gas emissions at a time when reductions are believed to be urgently needed to stabilize global climate change. By 2050 China will consume an estimated 17 percent of global energy demand. Chinese energy demand impacts global energy security as China's foreign policy agenda involves strategic partnerships with key energy suppliers.